ANALISIS FRAMING PEMBERITAAN KASUS PENJUALAN BURUNG BAYAN PADA ANTARANEWS KALBAR DAN SUARA PEMRED KALBAR - Rahma Fadhila; Hotma Simanjuntak; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research was conducted by analyzing the news to describe the framing of demonstration and court of Bayan sales case news from kalbar.antaranews.com and suarapemredkalbar.com. The research approach method is a descriptive method with a qualitative research form. The data sources of this research are the websites Antaranews Kalbar and Suara Pemred Kalbar. The research method is document analysis. There were 15 news articles analyzed. This research found that Antaranews Kalbar frames their news by two perspectives from Jum sides and law enforcer. Meanwhile, Suara Pemred Kalbar frames their news humanistically by Jum sides and they show the effort of Jum sides with Sambas Government to give him legal assistance.